Raising awareness of clinical trials in dementia: A national survey testing concept designs tailored to African American caregivers and individuals at risk: Health services research / Services. (7th December 2020) - Massett, Holly A; McGowan, Melissa; Han, Sae H; Watson, Jennifer; Emmerson, Karen; Burns, Adam; Robinson, Candice Watkins; Hummel, Allyson; Silverberg, Nina; Elliott, Cerise L; Donley, Grayson; Bernard, Marie A
Abstract: Background: Low enrollment of African Americans into clinical trials for Alzheimer's Disease (AD) and related dementias (ADRD) is partly a result of too few researchers offering trial opportunities and inadequate information that is culturally relevant. The National Institute on Aging (NIA) sought to develop a culturally acceptable/effective toolkit of AD/ADRD clinical trial (CT) outreach materials for community health professionals to use with African American audiences. This abstract presents the results of a national online survey testing several AD/ADRD concept designs with adults/caregivers to guide the toolkit's development. Method: An online national panel survey was conducted with African American adults who: 1) had a family history of AD/ADRD (n=206); 2) had no family history of AD/ADRD (n=204); and, 3) were caregivers of persons with AD/ADRD (n=206). Respondents reported their AD/ADRD and CT knowledge/attitudes/intentions; they reviewed four concept designs and indicated preferences/likelihood of each concept to impact five variables (visit website, interest in trials, attention, believability, salience). Concepts featured messages that tested well in focus groups. Result: Caregivers and those at‐risk self‐reported higher familiarity with AD/ADRD signs/symptoms than those with no family history; all groups self‐reported limited understanding of CTs. Two concepts ranked highest among all participants: emphasizing helping future generations and noting that AD/ADRD affects races differently. Most caregivers (61‐87%) and at‐risk participants (46‐89%) gave favorable scores for all impact variables across all concepts, indicating they found most concepts motivating and acceptable. Those with no family history provided lower impact scores (39‐78%). After viewing all concepts: all groups significantly increased (p<.05) their "interest in participating in clinical trials"; and, the at‐risk and no‐history groups were significantly more likely to disagree with "there is nothing I can do to reduce my risk of [AD]". Conclusion: This research identifies effective AD/ADRD ad concepts that are culturally tailored and acceptable to African Americans nationally, and addresses a known obstacle to recruitment. The combination of the messages/images successfully increased interest in CTs as an option to address AD/ADRD. Using these findings, NIA developed and offers an outreach toolkit to assist community health professionals who do not otherwise have resources to develop their own materials.